Changing the inflation target in emerging markets: the reward of reducing risk - (:unkn) unknown (My University, 2023)
This paper analyses the effects of change by the South African Reserve Bank (SARB) in its preferred definition of inflation target in July 2017 from a range to a point target. We estimate the implications of this shift by means of a Bayesian vector autoregression-based counterfactual exercise. Our results show that the inflation target change allowed to reduce prices and inflation expectations without negative effects on real output and employment. This was achieved via the reduction in the South African – US long-term interest rate spread (i.e. by a reduction in risk) and by a subsequent positive effect on asset prices.
Keywords: African Research